THE ROLE OF ALTERNATIVE ENERGY IN THE STRUCTURAL TRANSFORMATION OF THE ECONOMY OF UKRAINE (Development Service Industry Management, 2025)
The article examines the role of alternative energy as one of the key areas of structural transformation in the national economy of Ukraine, within the context of a protracted military crisis and the expected post-war recovery. The current economic challenges facing the energy sector during the period of Russian armed aggression are analyzed, specifically the systemic destruction of centralized infrastructure, the increased vulnerability of energy facilities, and the destabilization of electricity markets. It is established that alternative energy, particularly projects based on renewable energy sources, has the potential not only to compensate for losses but also to offer a new model of energy dynamics that can support the institutional, technological, and socio-economic renewal of the state. The emphasis is on decentralizing generation, regional management of energy resources, and increasing the economic autonomy of united territorial communities, particularly in frontline and affected regions. The importance of local energy initiatives as a tool for socio-economic stabilization, small business development, investment attraction, and energy poverty reduction is revealed. A SWOT analysis and classification of strategic directions for the post-war restoration of the energy system are presented, taking into account the principles of a green economy, security, and technological flexibility. The need to rethink the role of renewable energy sources, not only in the energy sector but also in the economic discourse, as an element of a new development paradigm capable of ensuring sustainable growth, integration into the European energy space, and the formation of a competitive business model, is substantiated. A vision of alternative energy as a driver of modernization changes is proposed, combining innovative technologies, institutional transformations, and community participation in strategic planning processes. It is emphasized that the transition to a new energy model can serve as the systemic basis for Ukraine's economic adaptation and long-term transformation in the post-war period.
Keywords: alternative energy; economic transformation; renewable energy sources; recovery economy; green energy